The intellectual and religious crisis of the modern educated Muslims: A study of Muhammad Kutb’s critique of colonial education policy in Muslim societies - Hasan, Md. Mahmudul (2012)
As regards complete submission to Islam and carrying out Islamic teachings in their entirety, the perplexity and confusion of a large section of modern educated Muslims is quite palpable. Skepticism about Islam of such educated Muslim elites has its root in colonial education policy and in what they have been taught at different levels of education. As Islam has the potential to motivate its adherents to stand for truth and justice, and against colonial oppression and exploitation, Muhammad Kutb (1919 – ) argues, colonial education policy was largely designed to deride Islamic principles, to destroy the sense of sanctity of Islam and to stereotype Islam in the most negative light. Such a policy was directed to creating a wedge between Muslims and their religious belief, moulding them on Western pattern and inculcating in them the values and passions of western civilization. As a result, in today’s Muslim world many of the best minds who could promote Islamic causes are bent on denigrating Islam and enthusiastic to promote and ‘parrot’ the imported thoughts of the West. In the light of this observation, I will analyze Muhammad Kutb’s critique of colonial policy and will argue that the current intellectual and religious crisis of the educated elite prevailing in Muslim societies vindicate his claim.]